Full characterization of the quantum linear‐zigzag transition in atomic chains. Issue 10 (31st July 2013) - Silvi, Pietro; De Chiara, Gabriele; Calarco, Tommaso; Morigi, Giovanna; Montangero, Simone; Blatt, Rainer; Bloch, Immanuel; Cirac, Ignacio; Zoller, Peter
<x xml:space="preserve">Abstract</x> A string of repulsively interacting particles exhibits a phase transition to a zigzag structure, by reducing the transverse trap potential or the interparticle distance. Based on the emergent symmetry ℤ2 it has been argued that this instability is a quantum phase transition, which can be mapped to an Ising model in transverse field. An extensive Density Matrix Renormalization Group analysis is performed, resulting in an high‐precision evaluation of the critical exponents and of the central charge of the system, confirming that the quantum linear‐zigzag transition belongs to the critical Ising model universality class. Quantum corrections to the classical phase diagram are computed, and the range of experimental parameters where quantum effects play a role is provided. These results show that structural instabilities of one‐dimensional interacting atomic arrays can simulate quantum critical phenomena typical of ferromagnetic systems. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>